Dynamics of Gadget Usage Behavior in Christian Religious Education Learning in Building Student Integrity in Grade XI of Isen Mulang High School, Palangka Raya - Marselina; Telhalia; Kilat Kasanang (EDUJAVARE: International Journal of Educational Research, 2026)
This study investigates the gap between Christian values taught in Christian Religious Education (CRE) and the digital behavior of Grade XI students at SMA Isen Mulang Palangka Raya, particularly regarding honesty, faithfulness, and responsibility. The issue was identified during the Field Experience Program (PPL), where organized academic dishonesty involving gadget use was observed. Using a descriptive qualitative approach, the research involved Grade XI students and a CRE teacher during the 2025/2026 academic year. Data were collected through classroom observations, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal three patterns of gadget use: adaptive, distractive, and predominantly ambivalent. These patterns are shaped by internal factors, including motivation and self-control, and external factors such as teaching strategies, peer influence, and school policies. Gadgets simultaneously support biblical learning and create opportunities for dishonest behavior, reflecting the complexity of students' digital experiences. The study concludes that strengthening digital integrity requires Christian digital literacy, consistent value internalization, effective self-regulation, and a supportive faith-based learning environment rather than prohibition alone.